Analisis Profil Suhu pada Greenhouse Tipe ARCH untuk Budidaya Bunga Krisan (Chrysanthemum morifolium) - Yuliasih, Ni Putu; Sumiyati, Sumiyati; Setiyo, Yohanes (Jurnal BETA (Biosistem dan Teknik Pertanian); Vol 4 No 1 (2016): Maret, 2016)
This research was describe about temperature profile on Arch Greenhouse with the curved shape of roof and square wall for Chrysanthemum (Chrysanthemum morifolium) that cultivated on Arch Greenhouse. The aims of this research were to obtain a temperature profile on arch greenhouse, to determine the building height of arch greenhouse which suit for chrysanthemum cultivation. Height treatments of greenhouse was separated by 3 levels i.e. 2.5 m, 3.0 m, and 3.5 m. Chrysanthemum seeds varietys used in this research was Fiji white. To measure the temperature used temperature and humidity meter. Temperature measurement carried out by 2 times start from a week before planting (empty condition) and plant age was 45 days after planting. Doing the measurement on morning, noon, and afternoon. Analysis data of temperature was done with interpolation to determine profile contour line of analysis temperature. The result showed that there are the different shape and contours distribution profile of microclimate for difference height. The level of growth plan on each treatments showed a better productivity on greenhouse with height 2.5 m when compared with the others. Greenhouse with height 2.5 m produced flower quality which suit as the SNI with average of height plan was 81.93 cm, grooming age was 46 days, amount flower was 5 florets per stem, flower wide was 44.26 cm, and dry weight was 13.11 gram.
Keywords: arch greenhouse, chrysanthemum